On the question of onomopragmatics (using the example of nickname names of architectural and residential buildings) (Eurasian Journal of Philology Science and Education, 2023)
Nicknames are a given part of anthroponymy, which is granted not only to peoples because of their beautiful features, but also to houses. The target of this note is the detection of skeletal as well as semantic distinguishing features of nicknames of construction and apartment buildings, the detection of key motivational properties of nicknames. Onomatology has close relationships with the situation, cultural studies, regional studies, philology, archaeology, linguistics. The academic significance of the activity consists in the typology of onomastic creations. The actual importance lies in the ability to apply the results of the study in the tasks of linguistics. Methods used: comparison, statistical calculation, semantic research. The study is able to provide a chance to establish the semantics of district toponyms. Why do multi-storey buildings need nicknames? There were constantly familiar structures of an extraordinary figure, similar as well as a figure. London Tower Bridge will soon become the most significant building in the UK. And, as this is established with the current skyscrapers, it has a name – "Shard". This is based on his figure. This name will connect to such unreasonable names, as well as Cucumber, Electric Shaver, Archive, Terochka for the purpose of cucumbers and also wet. The piece was planned in a fragment of a napkin in a Berlin restaurant by architect Renzo Softly in 2000.. He was inspired by the metal tracks, the English spires of the Venetian painter Canaletto, as well as the masts of the ships of the past.Key words onomastic, onomopragmatics, nicknames, culturology